Development of GIS-based traffic simulation on the Jakarta’s highway - Sediono, Wahju (2007)
One serious problem in Jakarta megacity is the daily traffic jam. Recently, according to the ever increasing amount of newly registered vehicles in Jakarta, the time interval needed to across some districts in Jakarta tends to be longer. The main reason for the traffic jam is the condition in which the road capacity and the arrival rate of vehicles are not staying in balance. Well planned traffic rules can be used to control the traffic flow so that the overload condition should never happen. To assist in the planning of these traffic rules, a traffic simulator has been developed at the Center for Information and Communication Technology in BPPT. By integrating a GIS-based digital road map into the above traffic simulator, the visualization of the simulation results can be enhanced significantly. In this paper some of the simulation results which are performed on the Semanggi’s highway section are presented. Further, the capability of this software-tool to support the management of Jakarta’s highway will also be figured out.